Science and narratives of nature
1 online resource (xi, 337 pages)
Keywords: "The discourse and practice of science are deeply connected to explicit and implicit narratives of nature. However, nature has been understood in diverse ways by cultures across the world. Could these different views of nature generate the possibility of alternate views on science' Part of the innovative series Science and Technology Studies, this volume looks at different conceptualizations of nature and the manner in which they structure the practice of the sciences. The essays draw upon philosophy, history, sociology, religion, feminism, mathematics and cultural studies, and establish a dialogue between cultures through a multi-disciplinary exploration of science. With contributions from major scholars in the field, this volume will deeply interest scholars and students of science and technology studies; sociology, history and philosophy of science; as also environmental studies."--Provided by publisher.